Working from home during the Covid-19 pandemic and its effect on employees and students - Piang, Thang Muan (Eximia, 2022)
The Covid-19 pandemic has modified our society’s daily life pattern. Businesses and firms, organizations, transportation, government patterns, and educational institutions were suddenly halted. People began working from home and shifted to remote working. This research is based on an investigation of multiple publications, journals, reports, and research papers. This study’s title is based on several employees and other related remote workers’ perspectives exploration and results. It aims to investigate the experience, challenges, effects, and perceptions of remote workers who work from home, student e-learning, and the crucial role of technology. It will also address the main research questions which is difficulties & issues, perspective view, convenience, emerging new technology and the impacts of work from home during the pandemic. The systematic literature approach and thematic analysis was applied in this study. Therefore, the findings’ authenticity is solid, accurate, and other various perspectives have been taken into account, and recommendations are provided.